The Distribution of Peak‐Ring Basins on Mercury and Their Correlation With the High‐Mg/Si Terrane. Issue 9 (9th September 2021) - Hall, G. P.; Martindale, A.; Bridges, J. C.; Nittler, L. R.; Bunce, E. J.
Abstract: A catalog of mercurian craters that retain their central peak or peak‐ring structure was created to aid target prioritization for the Mercury Imaging X‐ray Spectrometer (MIXS), now on its way to Mercury aboard BepiColombo. Preliminary analysis of the MIXS crater catalog suggested a potential spatial correlation between an abnormally high spatial density of peak‐ring basins and a region of Mercury with elevated Mg/Si values (High‐Magnesium Terrane [HMT]). Robust statistical analysis of previously published crater catalogs confirmed that the spatial correlation exists, with an overall confidence level of 97.7%, specifically between peak‐ring basins and the HMT, delineated by a contour of Mg/Si = mean + 2 σ  = 0.648. Applying empirical impact cratering scaling laws to the 15 basins intersecting the HMT suggested that all have excavated material from ~13 to 20 km depth. None of the basins excavated mantle material, predicting instead that deep crustal material contains elevated Mg/Si material. However, five of the basins are predicted to have melted underlying mantle material, which might be a contributing factor in the elevated Mg/Si signature. In the absence of resolvable volcanic features associated with the rise of basaltic melts from the mantle, we favor excavation of deep crustal, high Mg/Si material. MIXS‐T is capable of spatially resolving individual features associated with peak‐ring basins and it is proposed that the 15 basins within the HMT are prioritized targets for MIXS, to test the hypothesis of exposed deep‐crustal material. Plain Language Summary: A catalog of craters that retain a central peak, or peak‐ring structure, was created in order to prioritize targets for the Mercury Imaging X‐ray Spectrometer on the BepiColombo mission. Preliminary analysis of this catalog revealed a potential spatial correlation between a region with an abnormally high spatial density of peak‐ring basins and a region with high Magnesium‐to‐Silicon ratios. Robust statistical analysis of previously published crater catalogs was used to confirm that the spatial correlation exists. Investigation of the depth of excavation for material ejected during impact indicates that the impacts within the main high Mg/Si terrane excavated deep crustal, rather than mantle, material of high Mg/Si ratio. Current X‐ray data do not spatially resolve the basin features to confirm these hypotheses but future observations by the Mercury Imaging X‐ray Spectrometer are capable of doing so. Key Points: There is a statistically strong spatial correlation between a group of 15 peak‐ring basins on Mercury and the high Mg/Si region Crater uplift modeling and an absence of associated volcanic landforms, suggest excavation of deep crustal material with high Mg/Si The High Mg/Si region will be a key target for Mercury Imaging X‐ray Spectrometer‐T on BepiColombo to test the model of deep crustal excavation